2019
DOI: 10.1002/ctpp.201900061
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of ignition threshold in proton‐carbon hybrid ignitor beam proposal

Abstract: We may improve plasma ignition quality in a conically guided proton fast ignition scheme by the application of an extra lower intensity, secondary carbon beam. According to the experimental measurements on the number of laser-accelerated ions, the temporal evolution of the hot spot electron, ion, and radiation temperatures was examined using three-temperature plasma model, in radiation pressure acceleration (RPA) mechanisms for a proton-Carbon beam configuration, E avg ≈ 10 MeV/nucleon. The hot spot ignition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…In order to ignite an imploded fuel, the incident beam must be irradiated the target at the times of less than the hydrodynamic equilibrium time (τ eq ) 60 . Otherwise, as the plasma target expands, it will not have the density required to initiate ignition procedure.…”
Section: Core Heating By the Laser-accelerated Aluminum Beammentioning
confidence: 99%
“…In order to ignite an imploded fuel, the incident beam must be irradiated the target at the times of less than the hydrodynamic equilibrium time (τ eq ) 60 . Otherwise, as the plasma target expands, it will not have the density required to initiate ignition procedure.…”
Section: Core Heating By the Laser-accelerated Aluminum Beammentioning
confidence: 99%
“…The latter was first clarified by Temporal in 2006, where the improvement of deuterium-tritium (DT)-fusion conditions was confirmed using the idea of a two-beam scheme [28]. Recently, with the advantage of multiple proton-carbon species produced through the laser-foil interaction, the hybrid ignitor fast ignition proposed by Mehrangiz and Khoshbinfar [35]. It has been shown that the multiple proton-carbon beam proposal reduces the beam energy to 8.42 kJ, which can efficiently save about 15% of ignitor energy, compared to the default 10 kJ.…”
Section: Introductionmentioning
confidence: 99%